2014
DOI: 10.1016/j.bbrc.2014.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt kinase activity suppresses entry and replication of influenza virus

Abstract: The possibility of the pandemic spread of influenza viruses highlights the need for an effective cure for this life-threatening disease. Influenza A virus, belonging to a family of orthomyxoviruses, is a negative-strand RNA virus which encodes 11 viral proteins. A numbers of intracellular signaling pathways in the host cells interact with influenza the viral proteins, which affect various stages of viral infection and replication. In this study, we investigated how inhibition of Akt kinase activity impacts on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 35 publications
0
61
1
Order By: Relevance
“…However, in spite of in vitro antiviral activity in this study the mTOR inhibitor everolimus had no effect in vivo (Murray et al, 2012). Hirata and coworkers found using a peptide inhibitor of Akt kinase they could suppress entry and replication of the mouse adapted PR8 virus into the A549 cell line, in contrast to BEZ235 which we found had no effect on entry and genome replication in human primary epithelial cells (Hirata et al, 2014) (Fig. 5C).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, in spite of in vitro antiviral activity in this study the mTOR inhibitor everolimus had no effect in vivo (Murray et al, 2012). Hirata and coworkers found using a peptide inhibitor of Akt kinase they could suppress entry and replication of the mouse adapted PR8 virus into the A549 cell line, in contrast to BEZ235 which we found had no effect on entry and genome replication in human primary epithelial cells (Hirata et al, 2014) (Fig. 5C).…”
Section: Discussionmentioning
confidence: 49%
“…Likewise we see that the transient increase in cMyc expression induced by influenza infection is ablated by BEZ235 treatment in both NHBE donors (Figure 5B). Akt and PI3K inhibitors can block viral entry in transformed cell lines (Hirata et al, 2014; Shin et al, 2007). Preventing viral entry could explain reduced viral titer, c-Myc expression, and altered PI3k/mTOR activity.…”
Section: Resultsmentioning
confidence: 99%
“…The RPPA study identified additional proteins that may be targeted by these miRNAs, such as miR-744 targeting of Akt or miR-124a and miR-24 suppression of GSK-3β, as both of these factors were previously shown to be important for influenza virus entry 56, 57. Other previously identified roles of these miRNAs in viral infection include miR-24 suppression of Kruppel-like factor 6, which is induced by RSV infection to induce cell-cycle arrest, 14 as well as the suppression of furin by miR-24, which is required for influenza virus activation, 58 and miR-124a attenuation of Japanese encephalitis virus (JEV) via targeting dynamin2, which is required for efficient JEV replication 59 .…”
Section: Discussionmentioning
confidence: 99%
“…We found EMF inhibited HA and NA activity ( Figure 3 ), implying that the inhibition of virus infection by EMF results from blocking the HA-sialic acid receptor interaction and NA activity in the early stages of infection. The PI3K/AKT signaling pathway regulates viral entry, and the inhibition of AKT kinase activity suppresses viral entry and replication (Ehrhardt et al, 2006; Hirata et al, 2014). We found that EMF treatment decreased AKT phosphorylation ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%